2014
DOI: 10.1128/jvi.00333-14
|View full text |Cite
|
Sign up to set email alerts
|

Alpha/Beta Interferon Receptor Signaling Amplifies Early Proinflammatory Cytokine Production in the Lung during Respiratory Syncytial Virus Infection

Abstract: Type I interferons (IFNs) are produced early upon virus infection and signal through the alpha/beta interferon (IFN-α/β) receptor (IFNAR) to induce genes that encode proteins important for limiting viral replication and directing immune responses. To investigate the extent to which type I IFNs play a role in the local regulation of inflammation in the airways, we examined their importance in early lung responses to infection with respiratory syncytial virus (RSV). IFNAR1-deficient (IFNAR1−/−) mice displayed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
162
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(176 citation statements)
references
References 48 publications
12
162
0
2
Order By: Relevance
“…Recent studies have shown that RSV infection of IFNAR-deficient mice leads to lower levels of inflammatory cytokines (52)(53)(54), and our data show that, similarly, IFNAR Ϫ/Ϫ mice infected with HMPV have fewer inflammatory cytokine transcripts. Histological analysis of infected animals showed significantly less lung inflammation in IFNAR Ϫ/Ϫ mice than in WT mice, and IFNAR Ϫ/Ϫ mice had significantly less lung dysfunction and weight loss during infection, suggesting that IFNAR signaling contributes substantially to the major disease symptoms associated with HMPV infection (1,9,55).…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies have shown that RSV infection of IFNAR-deficient mice leads to lower levels of inflammatory cytokines (52)(53)(54), and our data show that, similarly, IFNAR Ϫ/Ϫ mice infected with HMPV have fewer inflammatory cytokine transcripts. Histological analysis of infected animals showed significantly less lung inflammation in IFNAR Ϫ/Ϫ mice than in WT mice, and IFNAR Ϫ/Ϫ mice had significantly less lung dysfunction and weight loss during infection, suggesting that IFNAR signaling contributes substantially to the major disease symptoms associated with HMPV infection (1,9,55).…”
Section: Discussionsupporting
confidence: 60%
“…The comparable RSV‐induced expression of Siglec‐1 on newborn and adult monocytes suggests a viral‐induced pathway that is already functional at birth. RSV‐induced expression of Siglec‐1 may be present on recruited monocytes and/or resident macrophages to regulate T cell functionality at the site of infection 9.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition or inadequate activation of T cells resulting in lower secretion of IFN‐γ may explain this high rate of reinfections 7, 8. Monocytes and T cells are both recruited to the site of RSV infection and the role of monocytes in the pathogenesis of RSV infections has been appreciated for decades 9, 10, 11, 12, 13, 14, 15. RSV increases the expression of major histocompatibility complex (MHC) molecules on monocytes, activates CD4 + T cells and induces the production of IFN‐γ by human immune cells In vitro 15.…”
Section: Introductionmentioning
confidence: 99%
“…When delivered to the lung, type I IFN in the lung was protective from C. burnetii infection in all tissues assessed, suggesting a tissue-specific response for the cytokine. Similarly, type I IFN promotes inflammatory responses in the respiratory tract following respiratory syncytial virus (RSV) infection (43). In contrast, during influenza virus infection, type I IFN decreased proinflammatory cytokines, which was directly linked to robust IL-10 expression.…”
Section: Figmentioning
confidence: 99%